Сорбционные свойства пористого дисперсного алмаза - Кулакова, И.И.; Корольков, В.В.; Карпец, А.В.; Ларионов, О.Г.; Лисичкин, Г.В. (Породоразрушающий и металлообрабатывающий инструмент – техника и технология его изготовления и применения, 2008)
The sorption-chromatographic properties of modified porous dispersed diamond (PDD) with H- and C₁₆H₃₃-groups on its surface have been studied by gas and liquid chromatography at the first time. Retaining times have been measured, adsorption isotherms have built, Genry constants and thermodynamic adsorption characteristics have been calculated. It has been indicated that two kinds of adsorption centers are present on PDD–Н surface. This surface is capable to the specific interactions more than PDD– C₁₆H₃₃ surface. The later sorbent is stable in high alkaline media.